2020
DOI: 10.3390/foods9030295
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Oxidation Kinetics of Extra Virgin Olive Oil (EVOO) and Shelf-Life Prediction

Abstract: Producers have to guarantee the extra virgin olive oil (EVOO) quality characteristics reported in the Regulation (CEE) 2568/91 throughout the product shelf-life (SL). Unfortunately, due to the development of oxidative reactions, some quality indices change during storage leading to a progressive deterioration of EVOO quality. To avoid the risk of product downgrading in the virgin oil category, the development of effective shelf-life prediction models is extremely important for the olive oil industry. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…Activation energy presented values consistent with data reported in literature for peroxide formation in sunflower oil [ 46 , 47 , 49 ]. Based on these sound results, the assessment of the sensory perception of rancid odor was selected as a proper quality indicator for the development of a shelf life model of crackers formulated with oil having different oxidation status.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Activation energy presented values consistent with data reported in literature for peroxide formation in sunflower oil [ 46 , 47 , 49 ]. Based on these sound results, the assessment of the sensory perception of rancid odor was selected as a proper quality indicator for the development of a shelf life model of crackers formulated with oil having different oxidation status.…”
Section: Resultssupporting
confidence: 89%
“…Results indicate that PV evolution is not consistent with the oxidation degree of the oil used for cracker formulation. As previously mentioned, the absence of a clear relation between oil oxidation level and the evolution of oxidation in crackers during storage could be related to the complex and interactive reactions at the basis of hydroperoxides formation and decomposition [ 35 , 36 , 45 , 46 , 47 ]. Although the rise of PV indicates a progressive quality decay of the products during storage, this indicator was not suitable for discriminating the quality profile of the cracker batches both just after production and during storage.…”
Section: Resultsmentioning
confidence: 99%
“…This trend can be explained by considering that PV decreases with the appearance of secondary oxidation products. During oxidation, the hydroperoxides can form and at the same time decompose; when the decomposition rate prevails, PV is lowered even before exceeding the legal limit if the temperature is high and the oxygen concentration low [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…K 270 is known to be a good marker of oxidation secondary stage because it is related to conjugated trienes and carbonyl compounds [ 25 ]. In a recent work, Conte et al [ 23 ] found that K 270 is the best index for allowing one to predict EVOO shelf life when an accelerated test is applied. For both EVOO cultivars, this parameter significantly ( p < 0.001) increased during storage, with significantly higher values in Bosana oil at 60 °C ( Table 1 ; Figure 4 ), as a logical consequence of the higher initial oxidation state of Bosana samples and the acceleration of chemical reactions at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Packaging technologies such as applying oxygen scavengers (Cecchi, Passamonti, & Cecchi, 2010) and light filtering packaging materials (Trypidis et al, 2019) can help better maintain the quality of oil under light, although they may become less effective when high concentrations of chlorophyll as prooxidant are present (Trypidis et al, 2019). Moreover, pyropheophytins have been reported to be very sensitive to temperature, another factor affecting the shelf-life of extra virgin olive oil, therefore these molecules can be used as a freshness parameter indicating exposure to temperature changes over 25°C (Conte et al, 2020).…”
Section: Introductionmentioning
confidence: 99%